Chemical processing of Bambara Groundnut Flour (Vigna subterranea) - Kremmyda, Alexandra (2020)
The first aim of this thesis was the determination of the crude protein content (21%), the fat (6.69%) and the moisture (8.85%) of a Bambara Groundnut Flour (BGF) trace called Ex - Sokoto. The microstructure of the BGF showed starch granules in the cotyledon cells surrounded by a protein matrix and fibrous material. Subsequently, BGF was treated with various solvents / pH conditions (H2O pH=6, alkalinised H2O pH=9 and 0.1M NaOH pH=13) in order to investigate the effect of different solvents on its physicochemical characteristics. Water Absorption Index (WAI) increase with lower pH treatment (H2O > alkalinised H2O > 0.1M NaOH) while the Solubility Index (SI) was higher at higher pH (0.1M NaOH > alkalinised H2O > H2O). The starch gelatinisation peak of the pellets resulting from the BGF treatment with different solvents, found at 80 - 85 oC. The particle size of the same samples showed a trimodal distribution with peaks at ≈ 50 µm (starch), 100 μm and 150 - 1,000 μm. The sample treated with alkalinised H2O presented the highest ability to solubilise the proteins. This was confirmed by SDS - PAGE and elemental analysis where the supernatant of this sample revealed the greatest number of bands and intensity and the highest crude protein content (45.45%). Protein isolates were prepared from BGF using alkalinised H2O (pH=9) and 0.1M NaOH (pH=13). The BCA assay test showed that the protein isolate extracted with 0.1M NaOH had higher content in “water soluble proteins” than the isolate extracted with alkalinised H2O. Elemental analysis showed that alkalinised H2O had higher crude protein content (86.08%) and greater intensity of bands at the SDS -PAGE profile in comparison to 0.1M NaOH protein isolate.